Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat Pembuatan KTP-e Di Dinas Kependudukan Di Pencatatan Sipil Kabupaten Seluma - Rahiman Dani; Sawihin Sawihin; Budiman Sakti; Henny Aprianty; Heru Purnawan (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Public services under the process of making an E-KTP in Indonesia are not yet uniform with different levels of quality and up in each region. The conditions there were because the achievements of the recording results were asked that the upward target had not been determined, the achievement of the targets had not been achieved because there was still weak coordination between our departments, elements up and down related to the recording process were asked. The same thing is known that people's motivation in the recording process is still low, especially people who live in rural areas. The satisfaction of the people in Seluma Regency who receive services for making electronic KTPs is largely determined by the quality of service for officers at the Dukcapil Office. The level of service satisfaction for making electronic ID cards is explained by the dimensions on the quality of public services (Zeithaml, 2013), on the dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The research problems found were (1) how is the community's response to the quality of public services in the process of making an E-KTP (2) Does the quality of public services affect people's satisfaction in making KTP-E at the Dukcapil Office of Seluma Regency. The analytical method used is multiple linear regression, the number of samples is 95 respondents. The results of the questionnaire were tested for validity and reliability as well as the classical assumption test to find out whether the resulting upward equation met the validity of the data. The Sturges interval scale in the study was to determine the perceptions of respondents, a partial test (t-test) was used simultaneously (F-test) to answer the proposed hypothesis. The results of research into (5) the dimensions of the quality of public services; reliability, responsiveness, assurance, empathy, and tangibles received a "Good" category response from the community in the process of making the KTP-E. Partial test results (t-test) on the dimensions of reliability (X1), Responsiveness (X2), and Tangibles (X5) obtained positive and significant results according to the Assurance (X3) and Emphaty (X4) dimension diagrams that have positive and significant results on community satisfaction. Simultaneous test results (F-test) also note that the quality of public services has a positive and significant effect on community satisfaction.